Examination of Heart Failure as a Predictor of Driving Cessation - Fausto, Bernadette A. (J Transp Health, 2017)
Cognitive dysfunction is a predictor of driving cessation in older adults and a common sequela of heart failure (HF). Although HF has been associated with an increased risk of driving cessation, the independent relationship between HF and driving cessation after cognitive function is considered remains to be established. The objective of these analyses is to examine HF as an independent predictor of driving cessation across three years among a cohort of older drivers in the United States. Analyses included 850 older adults who completed sensory, cognitive, and physical measures at baseline and mobility and health measures at a three-year follow-up. Cox regression was used to examine the effects of HF, stroke, vision, cognition, and physical function as predictors of incident driving cessation over three years. Participants with HF were over three times more likely to cease driving, HR = 3.19, 95% CI [1.27, 8.02], p = .014. However, HF was no longer a significant predictor of driving cessation when cognitive performance was considered, HR = 1.70, 95% CI [0.67, 4.30], p = .262. These findings suggest that the risk of driving cessation may be a consequence of the cognitive dysfunction associated with HF, rather than from HF itself. Cognitive training should be investigated among persons with HF to potentially prolong driving mobility.